Implementasi Pelatihan Manajemen Keuangan Sederhana untuk Meningkatkan Kemandirian Usaha PKK Desa Landungsari - Alfiana; Anam Choirul; Gatot Soebiyakto (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
PKK groups in rural areas have significant potential in developing home-based micro-enterprises; however, limited financial literacy often becomes a major constraint in achieving sustainable business management. This community service program aimed to enhance the business independence of PKK groups in Landungsari Village through simple financial management training focusing on daily transaction recording, cost of production (COP) calculation, and pricing determination. The program was implemented through four stages: needs assessment, training module development, training implementation combined with on-site mentoring, and outcome evaluation. The results indicated a substantial improvement in participants’ understanding of basic financial management concepts. All participants were able to apply daily cash bookkeeping, with recording accuracy increasing from 65% in the first week to 92% in the third week. Furthermore, most participants began separating personal and business finances, calculating the cost of production, and setting more rational selling prices. On-site mentoring played a critical role in strengthening the consistency of financial recording practices and encouraging behavioral changes toward more professional business management. In conclusion, simple and context-based financial management training effectively improved the financial literacy and business independence of PKK groups. The program demonstrates that practical and participatory approaches can significantly strengthen women-led micro-enterprises. Continuous mentoring and follow-up training are recommended to ensure the sustainability of financial management practices within PKK-based businesses.